Rice Price Market Integration and Supply Chain Management (SCM) in Indonesia - Makbul, Yogi; Limakrisna, Nandan; Ratnaningtyas, Sudrajati; Rochana, Siti Herni (International Journal of Supply Chain Management, 2020)
The purpose of this research is to analyze rice market integration and SCM among major cities in Indonesia. The data are the average monthly rice prices in 33 major cities from January 2014 to December 2017 taken from the Central Statistics Bureau of Indonesia. The research methods are non–time series analysis and time series analysis. The results from the non–time series analysis show that almost all rice prices have significant market integration, but a few cities do not. The time series analysis covers only a few of the cities included in the research; however, due to the requirement that the Error Correction Model (ECM) data must be stationary. The results from the time series analysis show that all cities analyzed have significant long-run integration, but in the short run, only a few cities have market integration. The results of this research can support government intervention in spreading the rice price in a few cities to other cities in Indonesia.